Penerapan Teknologi Metaverse pada Bank Syari’ah - Slamet Riyadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Computer Science innovation plays a major role in everyday life-changing and enriching human interaction, communication, and social transactions. Currently, the fourth wave of computational innovation is underway relating to spatial (mapping), immersive technologies such as Virtual Reality (VR), and Augmented Reality (AR). Metaverse is a new interface that is expected to be used to perform all kinds of human-computer interactions. Bank BRI and Bank Mandiri are conventional banks that are starting to enter the metaverse ecosystem. Of the features that have been provided by BSI, there are no features related to the metaverse. From the search that the author did from various sources,untill now there has been no Islamic bank in Indonesia that has begun to penetrate the world of the metaverse. In this article, the focus of the discussion is on the metaverse application that can be used for virtual branch offices of Islamic banks. With the virtual branch in Metaverse, of course, it is hoped that it can be a new, fun journey for customers while at the same time being able to reach a wider community to carry out various digital transaction services as well as better customer service in the future. Spatial is one of the most worthy metaverse applications for the banking world, including Islamic banks. Spatial application provides features that can serve customers in the metaverse realm at a low cost. Spatial empowers users to take advantage of beautiful privacy spaces to share engaging content, build close-knit communities, and drive meaningful sales of creative works and products. Keywords: Augmented Reality, Metaverse, Islamic banking, Virtual Branch, Spatial.